Pengaruh Citra Perusahaan dan Kepuasanpelanggan terhadap Loyalitas Pelanggan pada Toko Bunga Pertiwi Cabang Sulanyah - I Gusti Bagus Kelvin Wira Yudha; Ni Nyoman Yulianthini (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to obtain tested findings about the effect of corporate image on customer loyalty, the effect of customer satisfaction on customer loyalty, and the effect of corporate image and customer satisfaction on customer loyalty. The research design used was causal quantitative research. The subjects in this study are consumers who have become customers of the Sulanyah branch of the Pertiwi Flower Shop and the objects in this study are company image, customer satisfaction, and customer loyalty. Data were collected by document recording and questionnaire method, and analyzed by multiple linear regression analysis. The results showed that 1) company image had a positive and significant effect on customer loyalty of Toko Bunga Pertiwi, 2) customer satisfaction had a positive and significant effect on customer loyalty of Toko Bunga Pertiwi, 3) company image and customer satisfaction had a significant effect on customer loyalty of Toko Bunga Pertiwi.